Solve -3*q + 2*a + 11 = -5, -2*q - 3*a = 11 for q.
2
Solve 0 = -3*b - 5*d - 6, 0 = -3*d + 4 + 5 for b.
-7
Solve -3*d + w - 8 = 0, d - 3*d + 2*w = 0 for d.
-4
Solve 4*a = 2*n + 12, 8*n + 3*a = 5*n + 9 for n.
0
Solve -2*y = -2*z + 4, -14*z - 10 = -16*z for y.
3
Solve -5*p - 7*g = -9*g + 17, -2*p - 26 = -4*g for p.
-1
Solve -3*m - 2*t + 17 = 3*t, 3*t = 12 for m.
-1
Solve 3*a + 9 = 5*a + 3*c, 3*c - 9 = 0 for a.
0
Solve 5*b - a + 8 = 0, 4*b = 2*b - 3*a - 10 for b.
-2
Solve 3*k = -2*m - 2, 5*k - 9*m + 10*m = -1 for k.
0